53.9k views
4 votes
"If a - 7 = b(x + 2), then x = ?"

Please help!!!!
I need a step by step explanation too.

"If a - 7 = b(x + 2), then x = ?" Please help!!!! I need a step by step-example-1

1 Answer

2 votes

Answer: choice (3), x = (2b+7)/(a-b)

==============================

Step-by-step explanation:

The idea is to get all the x terms to one side (after distributing), then factoring out the common term x, finally divide both sides by (a-b) as shown below

ax-7 = b(x+2)

ax-7 = bx+2b .... distribute

ax-7+7 = bx+2b+7 ... add 7 to both sides

ax = bx+2b+7

ax-bx = bx+2b+7-bx ... subtract bx from both sides

ax-bx = 2b+7

(a-b)x = 2b+7 .... factor out the GCF x

x = (2b+7)/(a-b) ... divide both sides by (a-b)

We have all of "2b+7" over "a-b" as one big fraction. This is what choice (3) is showing.

User Chris Gillatt
by
5.7k points